Comparative Analysis of Framing in Digital Media Narratives on the Issue of National Data Center Hacking - Istiani, Ade Nur; Cahyati, Emma Nur (Future Science, 2026)
The hacking of the National Data Center (PDN) in June 2024 had a serious impact on public services, data security, and public trust in the government's digital systems. This incident received widespread coverage from online media outlets such as Kompas and Detik, which, through their respective framing of the news, formed different narratives about the causes, responsibilities, and implications of the issue. This study uses qualitative methods and Robert N. Entman's framing analysis approach. The results of this study show differences in the framing used by Kompas and Detik. Kompas tends to criticize the government's negligence in addressing the cyber-attack. Meanwhile, Detik emphasizes that the hacking issue was caused by external attacks. The analysis results show that media framing plays an important role in shaping the dominant narrative and public perception regarding the hacking incident.